2018
DOI: 10.1097/rli.0000000000000413
|View full text |Cite
|
Sign up to set email alerts
|

Unenhanced Dual-Energy Computed Tomography

Abstract: Brain edema reconstructions are able to more accurately detect edema and end-infarct volume as compared with initial TNC images. This provides a better assessment of the degree and extent of infarction and may serve to better guide therapy in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 41 publications
0
34
0
Order By: Relevance
“…39 On the other hand, CT signs of brain swelling without concomitant parenchymal hypoattenuation in patients with acute cerebral ischemia may suggest ischemic penumbral or oligemic tissue as evaluated by diffusion and perfusion studies. 40 Methods to differentiate between infarct volume and perilesional edema using CT include identifying net water uptake 41,42 and dual-energy CT. 43 In our study, perilesional edema was differentiated from ischemic areas by comparing MRI diffusion weighted imaging with CT as has been demonstrated before. 44,45 As penumbra cannot be differentiated from edema beyond doubt, 44,45 it was considered a part of the edema.…”
Section: Focal Cerebral Ischemiamentioning
confidence: 77%
“…39 On the other hand, CT signs of brain swelling without concomitant parenchymal hypoattenuation in patients with acute cerebral ischemia may suggest ischemic penumbral or oligemic tissue as evaluated by diffusion and perfusion studies. 40 Methods to differentiate between infarct volume and perilesional edema using CT include identifying net water uptake 41,42 and dual-energy CT. 43 In our study, perilesional edema was differentiated from ischemic areas by comparing MRI diffusion weighted imaging with CT as has been demonstrated before. 44,45 As penumbra cannot be differentiated from edema beyond doubt, 44,45 it was considered a part of the edema.…”
Section: Focal Cerebral Ischemiamentioning
confidence: 77%
“…It showed that the X-Map (brain edema image) is able to detect edema and measure the end-infarct (core infarct) volume more accurately than conventional CT does. The sensitivity, specificity, positive predictive value, and negative predictive value of the X-Map (brain edema image) were 93.3, 100, 100, and 91.7%, respectively, while those of conventional CT were 80, 72.7, 80, and 72.7%, respectively [29].…”
Section: X-map Algorithmmentioning
confidence: 94%
“…The study found that acute infarctions delineated by the X-Map agreed very well with those by diffusion-weighted images, including ischemic regions that recovered after treatments. Another study [29] compared X-Map (brain edema image) with conventional CT using a 24-h follow-up CT as the gold standard. Mohammed et al called these processed images brain edema images.…”
Section: X-map Algorithmmentioning
confidence: 99%
“…To improve treatment, some studies have used Dual-energy CT to predict lesions [7,8], which is based on high and low peak voltage acquisitions, but is presently not conducted in China. There are also studies that have detected damaged brain tissue early after cerebral ischemia using multimodal CT techniques (CT angiography and CT perfusion, with source images) [9,10], which have been shown to have similar sensitivity to MRI [8]. However, none of these methods are as convenient and as easy to use as noncontrast CT (ncCT).…”
Section: Introductionmentioning
confidence: 99%